Study protocol for HGCSG1801: A multicenter, prospective, phase II trial of second-line FOLFIRI plus aflibercept in patients with metastatic colorectal cancer refractory to anti-EGFR antibodies - Nakatsumi, Hiroshi; Komatsu, Yoshito; Muranaka, Tetsuhito; Yuki, Satoshi; Kawamoto, Yasuyuki; Harada, Kazuaki; Dazai, Masayoshi; Tateyama, Miki; Sasaki, Yusuke; Miyagishima, Takuto; Tsuji, Yasushi; Katagiri, Masaki; et al. (Frontiers in Oncology, 2022)
Background: The first-line chemotherapy for patients with RAS and BRAF wild-type metastatic colorectal cancer (mCRC) commonly involves cytotoxic regimens, such as FOLFOX and FOLFIRI, combined with epidermal growth factor receptor (EGFR) antibodies. When progression occurs following anti-EGFR antibody-combined chemotherapy, anti-angiogenic inhibitors can be used as second-line treatment. Although randomized controlled trials have shown that anti-angiogenic inhibitors [bevacizumab, ramucirumab, and aflibercept (AFL)] carry survival benefit when combined with FOLFIRI as second-line chemotherapy, such trials did not provide data on patients with mCRC refractory to anti-EGFR antibody-combined chemotherapy. Therefore, our group planned a multicenter, nonrandomized, single-arm, prospective, phase II study to investigate the safety and efficacy of FOLFIRI plus AFL as a second-line chemotherapy for patients with mCRC refractory to oxaliplatin-based chemotherapy combined with anti-EGFR antibodies. Methods: FOLFIRI (irinotecan 180 mg/m2, l-leucovorin 200 mg/m2, bolus 5-FU 400 mg/m2, and infusional 5-FU 2400 mg/m2/46 h) and AFL (4 mg/kg) will be administered every 2 weeks until progression or unacceptable toxicities occur. The primary endpoint will be the 6-month progression-free survival (PFS) rate, whereas the secondary endpoints will include overall survival, PFS, response rate, disease control rate, adverse events, and relative dose intensity for each drug. A sample size of 41 participants will be required. This study will be sponsored by the Non-Profit Organization Hokkaido Gastrointestinal Cancer Study Group and will be supported by a grant from Sanofi. Discussion: There is only an observational study reporting data on FOLFIRI plus AFL for patients with mCRC who previously received anti-EGFR antibodies; therefore, a prospective clinical trial is needed. This study will prospectively evaluate the efficacy and safety of FOLFIRI plus AFL in patients with mCRC who are resistant to anti-EGFR antibodies and have limited data. Moreover, this study will reveal predictive biomarkers for AFL-based chemotherapy. Trial registration: Japan Registry of Clinical Trials, jRCTs011190006. Registered 19 November, 2019, https://jrct.niph.go.jp/latest-detail/jRCTs011190006.